Tanggung Jawab Negara Peluncur Terhadap Pengelolaan Sampah Antariksa Dalam Kerangka Hukum Internasional - Fitrah Aulia, Zahra; Michael, Tomy (CV. Era Digital Nusantara, 2023)
This research discusses the responsibilities of launching states in the management of space debris within the framework of International law. The advancement of technology has given rise to a new form of technology known as space technology, or commonly referred to as human-made space objects. The presence of these space objects has had a positive impact on human life on Earth, but it has also undeniably created new challenges in the form of environmental changes in outer space due to the accumulation of space debris resulting from space activities. With an increasing number of human-made space objects being launched into space, there is a risk of space debris accumulation in Earth's orbit, potentially threatening the safety and sustainability of space activities. Currently, there is no specific international regulation governing the management of space debris, which can lead to ambiguity in the responsibilities of states regarding space debris management. Therefore, this research employs a normative approach by examining various legal documents related to space activities, with a focus on the Treaty on Principles Governing the Activities of States in the Exploration and Uses of Outer Space, including the Moon and Other Celestial Bodies, 1967 (Outer Space Treaty 1967) and the Convention on International Liability for Damage Caused by Space Objects (Liability Convention 1972). The objective of this research is to determine whether states bear responsibility for the management of space debris.